Principles of Neurosurgery (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Neurosurgery is a vast subspecialty in medical sciences. A brief textbook covering all aspects of neurosurgery is probably rare, especially for postgraduate students, undergraduate students as well as general physicians. The available neurosurgery textbooks are either very detailed or do not cover all parts of neurosurgery. This book is going to be very useful to those who will be sitting for a neurosurgery postgraduate examination/board examination or looking for concise ideas on neurosurgery. This book is based on recent and established scientific data, covering all parts of neurosurgery that can help them a lot including practicing neurosurgeons and neuroscientists as well. Here more emphasis will be given to common neurosurgical conditions without ignoring less frequent conditions.